2009
DOI: 10.1136/bjo.2009.161059
|View full text |Cite
|
Sign up to set email alerts
|

In vivo confocal microscopy of conjunctival goblet cells in patients with Sjogren's syndrome dry eye

Abstract: Tear film function test showed that all patients had moderate to severe dry eye. The GC in LSCM images was characterised as a large hyper-reflective oval-shape cell with relatively homogeneous brightness. Though GC density assessed by LSCM (332 ± 137) cells/mm² was higher than that measured by impression cytology (200 ± 141) cells/mm², they showed a significant positive correlation, ρ = 0.908 (p < 0.05). Conclusion Conjunctival GC could be easily discriminated under the LSCM. LSCM may be a valuable tool in mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 22 publications
2
49
0
Order By: Relevance
“…25 Goblet cell density assessment using LSCM has been used to assess ocular surface changes related to age, 26,27 Sjögren's syndrome DE, 2,19 pterygium, 28 chemical burns, 29 glaucoma treatment with preserved and unpreserved levobunolol, 30 and tafluprost therapy. 31 To date, only one cross-sectional report of GCD assessed by LSCM in CLW has been published, which showed no significant difference between CL wearers and non-CL wearers; however, that study was limited by small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Goblet cell density assessment using LSCM has been used to assess ocular surface changes related to age, 26,27 Sjögren's syndrome DE, 2,19 pterygium, 28 chemical burns, 29 glaucoma treatment with preserved and unpreserved levobunolol, 30 and tafluprost therapy. 31 To date, only one cross-sectional report of GCD assessed by LSCM in CLW has been published, which showed no significant difference between CL wearers and non-CL wearers; however, that study was limited by small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…2 Conjunctival Impression Cytology. A few minutes after performing LSCM, the same eye was anaesthetized again and the center of a Biopore membrane (Millicell cell culture inserts; Millipore Corp, Cork, Ireland) was gently applied to the nasal bulbar conjunctival surface at approximately 2 to 4 mm from the limbus.…”
Section: Goblet Cell Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…We used IVCM because this technique is minimally invasive, and it is effective in evaluating the histopathology of surface disease (Mastropasqua et al 2006;Messmer et al 2006;Hong et al 2010;Le et al 2010;Wakamatsu et al 2010;Zhu et al 2010) and the toxic effects of glaucoma therapy (Arici et al 2000;Messmer et al 2006;Ciancaglini et al 2008;Martone et al 2009;Bergonzi et al 2010). Our study showed that no changes occurred throughout followup in both controls and patients treated with preservative-free timolol; on the opposite, BAK-preserved eye drops were associated with signs of ocular surface inflammation (lower goblet cell density and epithelial irregularity) after 12 months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the most reliable method for analyzing GCs in vivo is laser scanning confocal microscopy (LSCM), a noninvasive in vivo technology that evaluates the ocular surface tissues at the cellular level, providing a valuable method to identify and characterize GC morphology in different OSDs including glaucoma-related OSD (14)(15)(16). Nevertheless, to date, no study was specifically dedicated to determining the effects of the commercially available classes of glaucoma medications, and their regimens, on the density of conjunctival GCs in patients with glaucoma.…”
mentioning
confidence: 99%